In-beam diamond start detectors - Ciobanu, Mircea; Berdermann, E.; Herrmann, Norbert; Hildenbrand, K. D.; Kis, M.; Koenig, W.; Pietraszko, J.; Pomorski, M.; Rebisz-Pomorska, M.; Schuttauf, A. (IEEE transactions on nuclear science, 2011)
This paper describes operation principles and the in-beam performance of Start Detector (SD) assemblies consisting of Diamond Detectors (DDs) grown by Chemical Vapour Deposition (CVD) and Front End Electronics (FEE) which have been designed for and used in various nuclear physics experiments at GSI Helmholtz Center for Heavy Ion Research in Darmstadt.